UNVEILING PATRIARCHAL DOMINATION: An Integrative Study of Injustice for Dani Tribe Women and the Tamar’s Tale - Sugianto Sugianto (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
Analyzing the similarities between Dani women and Jewish women who are bound by patriarchal culture, the author will use an integrative approach to the second principle of Pancasila and Genesis 38:1–30 to prove that both care for women who are oppressed by patriarchal culture. By using Farnsworth's approach, the author proves that even though the context is different, both the second principle of Pancasila and Genesis 38:1–30 have common ground that supports each other in protecting women from patriarchal injustice. The most important contribution of this approach is providing strong support for the struggle to protect women who are vulnerable to patriarchal domination, both in the context of the Dani tribe and Jewish women as depicted in Genesis 38:1–30. By strengthening cooperation between the values of Pancasila and the principles expressed in the holy book, this approach provides a solid foundation for advocacy and real action to protect women's rights and end injustice caused by patriarchal culture. Menelaah kesamaan situasi antara perempuan suku Dani dengan perempuan Yahudi yang terikat oleh belenggu budaya patriarki, penulis akan menggunakan pendekatan integrasi antara sila kedua Pancasila dan Kejadian 38:1-30 untuk membuktikan bahwa keduanya mempunyai kepedulian terhadap pembelaan perempuan yang tertindas dan terbelenggu oleh budaya patriarki. Dengan pendekatan integratif Farnsworth terhadap sila kedua Pancasila dan Kejadian 38:1-30, penulis membuktikan bahwa meskipun mempunyai konteks masing-masing, namun baik sila kedua Pancasila maupun Kejadian 38:1-30 mempunyai titik temu yang saling berhubungan dan saling melengkapi dalam bentuk sebuah kesatuan fokus untuk memberikan perlindungan kepada perempuan yang mengalami ketidakadilan akibat belenggu budaya patriarki.